2008
DOI: 10.1080/08858190802247762
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life After Thyroid Cancer: An Assessment of Patient Needs and Preferences for Information and Support

Abstract: Patient care following thyroid cancer treatment could be improved by providing ongoing education about lifestyle factors related to cancer risk, disease surveillance, and resources for treating and coping with cancer. Health care providers should become familiar with local and Internet-based sources of information and support related to thyroid cancer to improve patient access to this information.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 19 publications
4
37
0
1
Order By: Relevance
“…A smaller, earlier survey examined quality of life, needs, and preferences for information and support in 62 TC patients (12). Although many patients reported good quality of life and felt they received adequate information throughout the course of treatment, most respondents delineated a desire for ongoing information resources, with particular regard to lifestyle habits that might affect recurrence, and symptoms of recurrence, which corresponds with some of the practical and medical questions in the present study that were largely unmet and that patient's expressed were important.…”
Section: Discussionmentioning
confidence: 99%
“…A smaller, earlier survey examined quality of life, needs, and preferences for information and support in 62 TC patients (12). Although many patients reported good quality of life and felt they received adequate information throughout the course of treatment, most respondents delineated a desire for ongoing information resources, with particular regard to lifestyle habits that might affect recurrence, and symptoms of recurrence, which corresponds with some of the practical and medical questions in the present study that were largely unmet and that patient's expressed were important.…”
Section: Discussionmentioning
confidence: 99%
“…The EORTC QLQ-C30 is one of the most commonly used questionnaires to evaluate HRQOL in various types of cancer. However, to the best of our knowledge, there has been only one report regarding HRQOL using EORTC QLQ-C30 in patients with DTC [27], in which the number of participants was small (n = 62), and the disease status and treatment modalities used for the patients were not specified. In this study we used a group of patients who were all disease-free and included a much larger total number of patients (n = 316).…”
Section: Discussionmentioning
confidence: 99%
“…Thyroid cancer, its diagnosis, and its treatment introduce physiological and psychological stressors that may negatively impact a patient’s quality of life (35). In a survey of 62 previously treated thyroid cancer patients, Roberts et al found that overall quality of life was high; however, 38.8% of patients reported concerns about recurrence (36). Patients also reported unmet information needs after treatment.…”
Section: Challenges To Implementation Of Active Surveillance Protocolsmentioning
confidence: 99%